2013
DOI: 10.4315/0362-028x.jfp-12-231
|View full text |Cite
|
Sign up to set email alerts
|

Observational Trial of Safe Food Handling Behavior during Food Preparation Using the Example of Campylobacter spp.

Abstract: Campylobacter infections are one of the most prominent worldwide food-related diseases. The primary cause of these infections is reported to be improper food handling, in particular cross-contamination during domestic preparation of raw chicken products. In the present study, food handling behaviors in Austria were surveyed and monitored, with special emphasis on Campylobacter cross-contamination. Forty participants (25 mothers or fathers with at least one child ≤10 years of age and 15 elderly persons ≥60 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
(33 reference statements)
2
9
0
Order By: Relevance
“…Among self‐reported behaviors for safe food handling, handwashing after toilet use was more consistently reported of the recommended practices evaluated (higher than 75%) including handwashing just prior to cooking. Use of a thermometer to measure the doneness of meat in cooking was the least consistently reported recommended safe food‐handling practice by 19% to 50% of the students or members of their households; however, previous studies have reported that fewer than 5% of consumers follow this recommended practice (Abbot and others ; Phang and Bruhn ; Hoelzl and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Among self‐reported behaviors for safe food handling, handwashing after toilet use was more consistently reported of the recommended practices evaluated (higher than 75%) including handwashing just prior to cooking. Use of a thermometer to measure the doneness of meat in cooking was the least consistently reported recommended safe food‐handling practice by 19% to 50% of the students or members of their households; however, previous studies have reported that fewer than 5% of consumers follow this recommended practice (Abbot and others ; Phang and Bruhn ; Hoelzl and others ).…”
Section: Resultsmentioning
confidence: 99%
“…As observational studies suggest, knowledge and self-reported behavior do not necessarily reflect the actual behavior (Behrens et al, 2010;Byrd-Bredbenner, Berning, Martin-Biggers, & Quick, 2013;Byrd-Bredbenner, Maurer, Wheatley, Cottone, & Clancy, 2007;DeDonder et al, 2009;Dharod et al, 2007;Fein, Lando, Levy, Teisl, & Noblet, 2011;Hoelzl et al 2013;Kindall et al, 2004;Phang & Bruhn, 2011;Worsfold & Griffith, 1997). However, an insight into what consumers know and what they need to be educated about can be obtained by such reported behavior .…”
Section: Introductionmentioning
confidence: 84%
“…Another study that involved preparing a chicken salad recipe found that only 57% of important hygiene measures ( i.e. , washing hands with soap and water, checking doneness with a thermometer) were used by participants [163]. …”
Section: How Can Health Professionals Help Consumers Handle Food Mmentioning
confidence: 99%